Analyzing Influences on Premarital Behavior Among Adolescents Through Cross-sectional Analysis: Efektivitas Intervensi Kalsium dan Aspirin dalam Pencegahan Preeklampsia - Siti Nur Azizah; Paramitha Amelia; Sri Mukhodim Faridah Hanum; Siti Cholifah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the factors influencing premarital sexual behavior among high school students at SMAN 1 Wonoayu. Findings reveal significant associations between knowledge, religiosity, peer influence, and technology with premarital sexual behavior. Recommendations include enhancing coordination between healthcare professionals and educational institutions to improve awareness and involving relevant government sectors in addressing this issue. Highlight: Factors: knowledge, religiosity, peers, technology affect premarital behavior. Cross-sectional study: high school students, analyze influencing factors. Recommendations: enhance coordination between sectors, address premarital behavior effectively. Keyword: premarital behavior, adolescents, influencing factors, knowledge, religiosity.